2014
DOI: 10.1074/jbc.m113.502351
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Enzymatic Control of α-Cleavage and β-Cleavage of the Prion Protein

Abstract: Background:The prion protein (PrP) is cleaved into bioactive fragments by enzymes and metal catalysis. Results: Key members of the ADAM protease family yield all observed PrP products. Conclusion: Proteases alone may be responsible for PrP processing, with distinct activities depending on specific enzymes. Significance: Elucidation of the responsible enzymes and products can be used to evaluate PrP function and proteolysis in prion disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 42 publications
4
99
3
Order By: Relevance
“…Our limited proteolysis experiments indicate that copper(II) binds to the N-terminal His residues of PrP within and outside the octarepeat domain at low metal/ligand ratios. Analogous results [115] have also been reported in a recent investigation, which shows that a member of the ADAM (a disintegrin and metallo proteinase) enzyme family, namely ADAM8, is able to cleave MoPrP C in a Cu 2+ dependent manner. Copper(II) coordination to His residues of the tetraoctarepeat domain and His110 has been found to suppress the cleavage of histidine peptide bonds.…”
Section: Resultssupporting
confidence: 79%
“…Our limited proteolysis experiments indicate that copper(II) binds to the N-terminal His residues of PrP within and outside the octarepeat domain at low metal/ligand ratios. Analogous results [115] have also been reported in a recent investigation, which shows that a member of the ADAM (a disintegrin and metallo proteinase) enzyme family, namely ADAM8, is able to cleave MoPrP C in a Cu 2+ dependent manner. Copper(II) coordination to His residues of the tetraoctarepeat domain and His110 has been found to suppress the cleavage of histidine peptide bonds.…”
Section: Resultssupporting
confidence: 79%
“…These results provide useful clues to understand the earlier onset of D178N-associated FFI diseases. It has been reported that reactive oxygen species (ROS) might mediate β-cleavage of PrP [16,[61][62][63], but there was no notable β-cleavage observed in our study. In the β-cleavage experiments studied in these reports, PrP samples were treated with H 2 O 2 and copper or other metal ion together, the generation of ROS is promoted by the presence of copper and iron through the Fenton reaction [61,64].…”
Section: Discussioncontrasting
confidence: 80%
“…108 and 109) and a recent study suggests a more complex scenario than initially expected, involving different members of the ADAM family of metalloproteases. 110 In contrast, the role of ADAM10 as the major PrP C sheddase has been established by recent studies. 95,96,107,111 While knowledge on the concrete localization of the two cleavage events is limited 54,111-113 both processing steps seem to depend on PrP C membrane attachment.…”
Section: Anchorage and Localization Of Prp C May Influence Its Proteomentioning
confidence: 99%